UJI TEKNIS ALAT PEMBUATAN MINYAK DAUN CENGKEH UNTUK INDUSTRI KECIL - Fidel C. A. Tendeng; Ireine A. Longdong; Dedie Tooy (COCOS, 2022)
ABSTRACTClove oil is one type of essential oil that can be obtained from the clove plant. Clove oil can be taken fromclove flowers or leaves. The oil content in clove flowers ranges from 17-18% while in the leaves is around 2-3%.Several equipments have been made to produce clove leaf oil, therefore in this study a technical test was carriedout for making clove leaf oil. The purpose of this research is to study the process of making clove leaf essential oilusing a distillation equipment in a bengkol production house, to vary the volume of kettle water and its effect onthe preheating time to the first drop of condensate, the duration of distillation, the temperature in the distillationprocess and the volume of clove oil resulting from. It is hoped that information on how to use and the right volumeof water will be produced in the clove leaf oil making equipments and how it affects the yield of clove oil producedcan be obtained. This study used an experimental method with three (3) treatments of different volumes of water ina kettle, PA: Water 10 liter , PB: Water 12.5 liter, and PC: Water 15 liter with two (2) times replicates for eachtreatment. The observation data on the effect of water in the boiler, the oil produced, the temperature in thedistillation process and the yield are presented in the form of figures and tables. The results showed that the higherthe volume of boiler water, the preheating time until the first drop of condensate increased. The volume of 10 literboiler water takes 60 minutes, while the boiler water volume of 12.5 and 15 liters takes 70 and 85 minutes. Thevolume of essential oil produced is increasing, the volume of kettle water is 10 liters, and the essential oil producedis 3 ml, while at the volume of 12.5 liter boiler water as much as 5 ml and 15 liters of water produces 7 ml ofessential oil. The highest yield is found in the volume of 15 liter boiler water, which is 0.558%, and the volume of12.5 liter boiler water produces a yield of 0.366% and the lowest yield is found in the volume of 10 liter boilerwater with a yield of 0.217%.Keywords: essential oil, clove, small industry, technical test